HOTS checker: Quick reviewing cognitive levels of learning outcomes using large language models - Baskara, Dwi Soca; Hardika, Hardika; Purwodani, Dio Lingga; Muttaqin, Nabil (Jurnal Inovasi Teknologi Pendidikan, 2024)
The development of tools for efficient and effective assessment of learning outcomes is crucial in education. However, identifying the appropriate cognitive levels for learning outcomes can be challenging for educators. This study proposes to develop a tool to address this challenge by combining the strengths of large language models (LLMs) and Bloom's taxonomy. The tool can benefit educators by providing them with a streamlined reviewing process and enhancing their ability to assess learning outcomes. This research referred to prototype development models by Pressman. The research stages included communication, quick plan, modeling and quick design, construction of prototype, delivery, and feedback. The validation process involved assessing the tool's accuracy, consistency, and potential to be implemented in real educational settings by educators. The overall score obtained from the validation process is 76.92%, with the highest results coming from the categories of the tool's potentiality. It demonstrates its potential as a valuable educational tool. The insights gained from the expert validation serve as a crucial guidepost for future iterations of the tool, aligning them more closely with the goals of enhancing learning outcomes in educational settings